Smart System for Stabilizing Water Flow Output on Android-Based Taps - Parenreng, Jumadi M; Zain, Satria Gunawan; Yusuf, Zulfatni; Suhardi, Iwan; Kaswar, Andi Baso (Internet of Things and Artificial Intelligence Journal, 2023)
This study aims to produce and find out the results of the Smart System Stabilization Water Discharge Output Test on Android-Based Faucets based on the results of water flow sensor readings whose data is used as a reference for the rotation of the Adj or Adjustable Water Pressure Reducing Regulator Valve. The tests were carried out in the form of measuring water flow without and with Adj and measuring water discharge without and with Adj. Based on the research results, the water flow without Adj is 7 L/min for tap 1.9 L/min for tap 2. The water flow with Adj for both taps is 8 L/min. The flow of water from both taps is more stable with Adj than without Adj because the flow of both taps is 8 L/min. The measurement results of the water discharge without Adj are 0.1216 L/s for tap 1 and 0.1470 L/s for tap 2; the difference in water discharge is 0.0254 L/s. Water debit with Adj 0.135 L/s tap 1 and 0.14125 L/s tap 2, the difference in water discharge is 0.00625 L/s. The water debit is more stable with Adj than without Adj because the difference in water discharge is smaller.